2000
DOI: 10.1095/biolreprod62.3.680
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Testis Interstitium of Sprague Dawley Rats from Birth to Sexual Maturity1

Abstract: Changes in the rat testis interstitium from birth to adulthood were studied using Sprague Dawley rats of 1, 7, 14, 21, 28, 40, 60, and 90 days of age. Our objectives were 1) to understand the fate of the fetal Leydig cells (FLC) in the postnatal rat testis, 2) to determine the volume changes in testicular interstitial components and testicular steroidogenic capacity in vitro with age, 3) to differentially quantify FLC, adult Leydig cells (ALC), and different connective tissue cell types by number and average v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
113
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 33 publications
14
113
4
Order By: Relevance
“…It is unclear if the complete population of COUP-TFII-expressing stem cells can develop into adult Leydig cells or only a subpopulation, because only a proportion of the stem cells switched on GATA4 or PDGFRα after EDS. Previous studies suggested that adult Leydig cells could originate from other interstitial cell types, such as peritubular myoid cells, pericytes, endothelial cells, or macrophages (24,29,(54)(55)(56). Using specific markers for these cell types and the EDS model, we found no evidence for coexpression of COUP-TFII in these cell types.…”
Section: Discussioncontrasting
confidence: 63%
“…It is unclear if the complete population of COUP-TFII-expressing stem cells can develop into adult Leydig cells or only a subpopulation, because only a proportion of the stem cells switched on GATA4 or PDGFRα after EDS. Previous studies suggested that adult Leydig cells could originate from other interstitial cell types, such as peritubular myoid cells, pericytes, endothelial cells, or macrophages (24,29,(54)(55)(56). Using specific markers for these cell types and the EDS model, we found no evidence for coexpression of COUP-TFII in these cell types.…”
Section: Discussioncontrasting
confidence: 63%
“…However, several studies suggested that PFLCs do not all enter apoptosis and degenerate but can persist in later puberty (Kerr and Knell, 1988;Ariyaratne and Chamindrani Mendis-Handagama, 2000;Ivell et al, 2003). Thus, the fate, function and the regulation of PFLCs after birth are still unknown, while testosterone production by PFLCs The present study has demonstrated a role for the cAMP-PKA transduction pathway in the regulation of Leydig-cell specific genes in PFLCs.…”
Section: Effect Of (Bu) 2 Camp and Paracrine Factors On Pflc Prolifermentioning
confidence: 52%
“…Early work suggested that fetal Leydig cells decline in number after birth due to either dedifferentiation or apoptotic cell death (Tapanainen et al, 1984;Byskov, 1986). Other studies have shown that the total number of the cells in the testis does not change markedly, but the number of Leydig cells per unit volume of testis decreases (Kerr and Knell, 1988;Ariyaratne and Chamindrani Mendis-Handagama, 2000). Whether, Leydig cell numbers are static or decline, androgen production decreases dramatically as the fetal Leydig cells undergo functional dedifferentiation starting in late gestation (Migrenne et al, 2001).…”
Section: Fetal Leydig Cellsmentioning
confidence: 99%